Variation in Formation of Renal Artery - gautam, Ajeevan; Khan, Gulam Anwer; Timilsina, Sameer; Dhungel, Deepesh; Sah, Sanjib Kumar (Journal of College of Medical Sciences-Nepal, 2020)
Backgrounds: Renal arteries are two large blood vessels branching laterally from the abdominal aorta just below the superior mesenteric artery. The arteries vary in their level of origin and caliber, obliquity and precise relations. Each renal artery is about 6-8mm diameter. There is a varying characteristic of these arteries owing to their different course. The aim of the study was to study the variation in the formation of renal artery with its branching pattern using CT Angiography. Methods: The study was conducted in the department of Radiology at Chitwan Medical College after obtaining ethical approval CMC-IRC. CT Angiogram was studied in 17 individuals who attended radiology department for angiography for different suspected abdominal and renal pathology. Results: Analyzing the result of the angiography we found the usual branching pattern of renal artery in 70.58% of the individual, with variations in remaining 29.42%. On studying the number of arteries supplying kidney, artery draining directly to hilum i.e. accessory renal artery was 2.95%. We found the average length of right renal artery ranged between 3.5cm to 6.0cm. Conclusions: The variations on this large lateral branch of abdominal aorta are common. Surgeons should exclude the possibility of presence of accessory and aberrant renal arteries obstruction prior to the surgical procedure. The awareness about the presence of such variations is important from the academic, surgical and radiological aspect.